Memahami Perspektif Lain Tentang Konsep Iman - Fadhila Sidiq Permana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Some scholars and intellectuals understand Faith and Islam more universally. They see that the value of faith can arise from the adherents of any religion. As long as a person has faith in his Lord and does righteous deeds. In the Qur'an even explained the existence of non-Muslims who believe, it will also be clearer when we look at historical literature and the book of interpretation. With this understanding we will be more mature in understanding differences and will not be easily triggered by conflicts in the name of religion.